Prevalence of sexual dysfunction in heterosexual patients attending a central London genitourinary medicine clinic. - Goldmeier,D; Keane,FE; Carter,P; Hessman,A; Harris,JR; Renton,A (Int J STD AIDS, 1997)
Our objective was to determine the prevalence of sexual dysfunction among new heterosexual attendees at a central London genitourinary medicine (GUM) clinic. We carried out a cross-sectional study in which patients completed a self-administered questionnaire-the Golombok-Rust Inventory of Sexual Satisfaction (GRISS) and participated in a brief interview during which additional information was sought regarding the patient's sexual history. An overall transformed score of >5 on the GRISS was defined as indicative of overall sexual dysfunction and a score of >5 on any of the subscales as indicative of a specific sexual dysfunction. Twenty-five (24%) men and 10 (9%) women had a GRISS score in keeping with overall sexual dysfunction, the prevalence being significantly lower in women (P=0.01, chi2=6.56, 1df). Sixty-three men (59%) and 63 (60%) women produced scores indicative of significant abnormality on at least one subscale, including, in men: erectile dysfunction 20 (19%), premature ejaculation 23 (22%), and in women: vaginismus 26 (25%) and anorgasmia 23 (22%). Neither an abnormal overall or subscale score on the GRISS was associated with a current STD on KC60 diagnosis or a history of sexual assault for either men or women. There is a substantial prevalence of sexual dysfunction in new heterosexual attendees at our clinic, the service implications of which need to be addressed.